Extraction, purification, microencapsulation and characterization of lipase from pumpkin (Cucurbita moschata Duchesne ex Poir.) seed - Mohd Hussin, Muhaini (2016)
Lipase is an enzyme with the presence of hydrolases act on ester bonds of triacylglerols. Most of the enzymes are easily degradable when expose to multistep process and expensive such as conventional purification. Hence it is important to establish and develop simple, low cost and environmental friendly system that could produce lipase to be used in industries such as food, detergent, pharmaceutical, biofuel industries. The pumpkin seed constitutes 30-37% of the whole pumpkin possesses valuable enzyme. Hence, pumpkin seed can be a potential novel source for the valuable and economical natural enzyme such as lipase. In this study, lipase was extracted from pumpkin (Cucurbita moschata) seed and the effects of the main factors affecting enzyme extraction namely, temperature, extraction time, pH of buffer, and buffer to sample (B/S) ratio were investigated for the development of the ultrasound-assisted extraction method. Optimum extraction condition was achieved at 5.5:1 (w/w) B/S ratio, 45 mins extractiong time, temperature 80 ºC and pH of buffer 8.0. The yield of the enzyme extracted was 80.1%. Subsequently, the potential application of novel aqueous two-phase system (ATPS) composed of Triton X-100 and xylitol in the purification of lipase from pumpkin seed crude was demonstrated at laboratory scale. In this part of the study, the effect of the main important parameters (such as volume ratio, crude load and pH) on purification of the enzyme was investigated. Optimum condition for purification of lipase from pumpkin seed was obtained After that, optimized extracted sample was purified using aqueous twophase system composed of 22% (w/w) and 25% (w/w) xylitol at 56.2% of tie line length (TLL) and 25% crude at pH 8.0 in order to obtain the purified enzyme. Based on the results it was demonstrated that the temperature TLL, volume ratio, crude load, and pH of buffer influenced the lipase partitioning. In ATPS, it was found that the molecular of lipase was estimated to be 39.2 kDA. Microencapsulation was performed using freeze-drying found that yield of freeze-dried in the trehalose (2%) and Arabic gum (5%) increased to 97.3% ± 0.3. It was found that during storage encapsulated lipase is stable by 95.2% ±0.1. The immobilized lipase was stable at 800C compared to the free enzyme, was around 500C. Characterization of the purified enzyme showed that lipase from pumpkin seed is stable in the presence of metal ions, surfactant and oxidizing agents. The lipase was stable 800C and pH 8 was found to be its optimum pH. The enzyme showed highest residual lipse activity on calcium chloride (CaCl2) and EDTA. Whereas, in substrate specificity, 4-nitrophenyl palmitate showed highest enzyme activity compared to corn oil, olive oil, soybean oil, and palm oil. It can be concluded that the valuable enzyme with unique characteristics from a rich, natural and cost-effective source could be made available for use in different types of industries such as food, detergents and also in biotechnological applications.